2007
DOI: 10.1186/1471-244x-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in Thai schizophrenic patients: a naturalistic one-year follow-up study

Abstract: Background: Not only the prevalence, but also the progress of metabolic abnormalities in schizophrenic patients is of importance for treatment planning and policy making. However, there have been very few prospective studies of metabolic disturbance in schizophrenic patients. This study aimed to assess the progress of metabolic abnormalities in Thai individuals with schizophrenia by estimating their one-year incidence rate of metabolic syndrome (MetS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 20 publications
10
34
2
Order By: Relevance
“…While two studies suggested that diabetes and obesity are more common (24,31), results of several studies argued against it (19,24,27,29,32,36). Hägg and colleagues (33), found higher prevalence of CVDs among families of patients with MetS, however, this was not replicated in two other studies (27,36).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…While two studies suggested that diabetes and obesity are more common (24,31), results of several studies argued against it (19,24,27,29,32,36). Hägg and colleagues (33), found higher prevalence of CVDs among families of patients with MetS, however, this was not replicated in two other studies (27,36).…”
Section: Introductionmentioning
confidence: 98%
“…There were no differences between schizophrenia patients with or without MetS in terms of family history of schizophrenic disorders (27), HT (19,24,27,29,32), dyslipidemia (19) and cerebrovascular disorders (29). While two studies suggested that diabetes and obesity are more common (24,31), results of several studies argued against it (19,24,27,29,32,36).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidence of metabolic syndrome A minority of studies calculated incidence rates of MetS [Attux et al 2007;L'Italien et al 2007;Saddichha et al 2007;Srisurapanont et al 2007;De Hert et al 2008b;Meyer et al 2008;Kim et al 2010;Kraemer et al 2010]. The results were hardly comparable in this field as incidence rates were calculated for various time periods, from 6 weeks up to 1 year.…”
Section: Metabolic Syndrome and Lifestyle Habitsmentioning
confidence: 99%